Pengembangan Bakat Dan Potensi Dakwah Santri Berbasis Teknologi Informasi Di masa Covid-19 Di Pondok Pesantren Putra-Putri Miftahul Mubtadiin Ar-Ridlo Krempyang Nganjuk - Syaiful Muda'i; Hafidhul Umami; M. Shohibul Aziz (Janaka, Jurnal Pengabdian Masyarakat, 2020)
The Santri at the Putra Putri Miftahul Mubtadiin Ar Ridlo Islamic Boarding School have sufficient talent and potential and are ready to be developed. With that capital, they can express their inspiration by looking at the environment around them. However, in applying it requires media. Therefore, a da'wah training program was carried out by utilizing information and communication technology during the Covid-19 period. With this program, the team hopes that the assisted partners will be able to develop their potential talents and spread them. The form of the program is in the form of da'wah training by utilizing information and communication technology during a pandemic using the ABCD method and the Service Learning approach. The results of the program have shown changes in the participants after initially not knowing how to preach by utilizing technology, after the training was held, they could summarize one hadith and write it as interestingly as possible. As a follow-up, the team hopes that after this program it will be continued by means of FK4 participants sending one hadith once a week, which will then be shared with the groups that the resource person is participating in.